Preoperative Risk-Stratification of High-Risk Prostate Cancer: A Multicenter Analysis - Chys, Brecht; Devos, Gaëtan; Everaerts, Wouter; Albersen, Maarten; Moris, Lisa; Claessens, Frank; De Meerleer, Gert; Haustermans, Karin; Briganti, Alberto; Chlosta, Piotr; Gontero, Paolo; Graefen, Markus; et al. (Frontiers in Oncology, 2020)
Background: Cancer-specific survival (CSS) within high-risk non-metastatic prostate cancer varies dramatically. It is likely that within this heterogenous population there are subgroup(s) at extraordinary risk, burdened with an exaptational poor prognosis. Establishing the characteristics of these group(s) would have significant clinical implications since high quality preoperative risk stratification remains the cornerstone of therapeutic decision making to date. Objective: to stratify high-risk prostate cancer based on preoperative characteristics and evaluate cancer specific survival after radical prostatectomy. Method: The EMPaCT multi-center database offers an international population of non-metastatic high-risk prostate cancer. Preoperative characteristics such as age, biopsy Gleason score, PSA and clinical stage were subcategorised. A multivariate analysis was performed using predictors showing significant survival heterogeneity after stratification, as observed by a univariate analysis. Based upon the hazard ratios of this multivariate analysis, a proportional score system was created. The most ideal group distribution was evaluated trough different score cut-off’s. The predictive value was tested by the herald C index. Results: An overall 5-year CSS of 94% was noted within the entire high-risk cohort (n = 4879). Except for age, all preoperative risk factors showed a significantly differing CSS. Multivariate analysis indicated, T4 stage as being the strongest predictor of CSS (HR:3.31), followed by ISUP grade 5 group (HR 3,05). A score system was created by doubling the hazard ratios of this multivariate analysis and rounding off to the nearest complete number. Multivariate analysis suggested 0pts - 4pts - 8pts - 12pts as being the most optimal group distribution (p-value: 0.0015). 5-year CSS of these groups were 97%, 93%, 87% an 70% respectively. The calculated Herald C-index of the model was 0.77. Conclusion: An easy-to-use pre-operative model for risk stratification of newly diagnosed high-risk prostate cancer is presented. The heterogeneous CSS of high-risk non-metastatic prostate cancer after radical prostatectomy is illustrated. The model is clinically accessible through an online calculator, presenting cancer specific survival based on individualised patient characteristics.